2018
DOI: 10.1186/s12891-018-2105-8
|View full text |Cite
|
Sign up to set email alerts
|

Micro-fragmented adipose tissue injection associated with arthroscopic procedures in patients with symptomatic knee osteoarthritis

Abstract: BackgroundThe social impact of degenerative diseases is steadily increasing, because of the continued rise in the mean age of the active population. Articular cartilage lesions are generally associated with disability and symptoms such as joint pain and reduced function, and remain a challenge for the orthopaedic surgeon. Several non-invasive solution have been proposed, but the results achieved to date are far from being completely satisfactory. Recently, new therapeutic approaches, such as the use of mesench… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
59
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 32 publications
9
59
0
1
Order By: Relevance
“…The development of new therapeutic strategies for the treatment of osteoarthritis is an active area of research. Recent human studies have demonstrated satisfactory results with the intra-articular administration of purified and micro-fragmented adipose tissue for the treatment of knee, 18,19 subtalar, 20 carpometacarpal 21,22 and thumb osteoarthritis. [23][24][25] In veterinary literature, a recent study 26 suggested clinical evidence of pain control over a period of up to 180 days with intra-articular administration of autologous purified and micro-fragmented adipose tissue for the treatment of osteoarthritis in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…The development of new therapeutic strategies for the treatment of osteoarthritis is an active area of research. Recent human studies have demonstrated satisfactory results with the intra-articular administration of purified and micro-fragmented adipose tissue for the treatment of knee, 18,19 subtalar, 20 carpometacarpal 21,22 and thumb osteoarthritis. [23][24][25] In veterinary literature, a recent study 26 suggested clinical evidence of pain control over a period of up to 180 days with intra-articular administration of autologous purified and micro-fragmented adipose tissue for the treatment of osteoarthritis in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…There are different methods to process autologous adipose into MFAT with minimal manipulation and avoiding the use of enzymes . Processed MFAT has been used as regenerative treatment for the management of musculoskeletal conditions such as knee osteoarthritis , shoulder pain secondary to osteoarthritis and rotator cuff tear , and osteochondral defects of the talus . In addition, case reports have reported improvement in pain and function scores after intra‐articular injection of MFAT in the setting of knee osteoarthritis and meniscal tear .…”
Section: Addressing the Treatment Gap—orthobiologicsmentioning
confidence: 99%
“…Cattaneo et al reported on 38 patients with knee OA who were treated with an arthroscopic procedure and an injection of autologous MAT. 53 They found a significant improvement in KOOS at 1, 3, 6, and 12 months follow-up, and reported that 92% of patients clinically improved, and 100% were satisfied with the treatment. However, as previously stated, there is still a paucity of evidence on MAT for the treatment of knee OA and other pathologies.…”
Section: Clinical Evidencementioning
confidence: 95%